2020
DOI: 10.1158/1538-7445.sabcs19-p6-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-14-13: New approach to nipple reconstruction: In vivo evaluation of acellular nipple-areolar complex grafts

Abstract: There are over 3M breast cancer survivors in the US, many of whom have undergone breast reconstructive surgery. With one-third of early stage and two-thirds of late-stage breast cancer patients opting for mastectomies without a standard, viable method to reliably reconstruct a permanent and natural nipple-areolar complex (NAC). NAC reconstruction is of key psychological importance for these patients, decreasing feelings of distress and increasing body image and self-esteem. Current NAC reconstruction options i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A proposed new solution is to take advantage of the extensive evidence that a decellularized allogeneic or xenogeneic graft, an acellular extracellular matrix scaffold, can serve as the nidus for a healing event when implanted in a human [ 2 ]. Although such scaffolds have long been derived from dermis, small intestinal submucosa, bladder and other organs, recent work has shown that deceased human donor nipples can be successfully decellularized and, when implanted on the surface of the body in a non-human primate model, exhibit complete healing within six weeks [1] . Planned clinical studies will bring this technology to humans, where longed for accurate and complete nipple restoration can be evaluated.…”
Section: Nipple Reconstructionmentioning
confidence: 99%
“…A proposed new solution is to take advantage of the extensive evidence that a decellularized allogeneic or xenogeneic graft, an acellular extracellular matrix scaffold, can serve as the nidus for a healing event when implanted in a human [ 2 ]. Although such scaffolds have long been derived from dermis, small intestinal submucosa, bladder and other organs, recent work has shown that deceased human donor nipples can be successfully decellularized and, when implanted on the surface of the body in a non-human primate model, exhibit complete healing within six weeks [1] . Planned clinical studies will bring this technology to humans, where longed for accurate and complete nipple restoration can be evaluated.…”
Section: Nipple Reconstructionmentioning
confidence: 99%